Flora Lyndsay; or, Passages in an Eventful Life : A Novel by Susanna Moodie - Moodie, Susanna, 1803-1885 (Book collections on Project MUSE., 2014)
Flora Lyndsay, a prequel to Susanna Moodie's Roughing it in the Bush and Life in the Clearings, presents a fictionalized record of her family's experiences in planning their emigration and crossing the Atlantic.